The Effect of Promotion of Bank Sumsel Babel Syariah Lubuklinggau Toward Community Saving Interest Lubuklinggau City West I - Oga Saputra; Lidia Desiana (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
This study aims to determine the interest of Lubuklnggau’s people to save, especially saving in a Sharia-based regional bank, namely Bank Sumsel Babel Syariah. This research was conducted for three months using primary data by distributing questionnaires, books and related journals, the location of the study was in the city of Lubuklnggau. The sampling techniques used in this research were random sampling techniques with a total sample of 0 respondents and analyzed with multiple linear regression. The results of this study show that Advertisements and Publicity affect people's saving interest, while sales promotion and personal sales did not affect people's.